2021
DOI: 10.14569/ijacsa.2021.0120610
|View full text |Cite
|
Sign up to set email alerts
|

Opinion Mining of Saudi Responses to COVID-19 Vaccines on Twitter

Abstract: In recent months, many governments have announced COVID-19 vaccination programs and plans to help end the crises the world has been facing since the emergence of the coronavirus pandemic. In Saudi Arabia, the Ministry of Health called for citizens and residents to take up the vaccine as an essential step to return life to normal. However, the take-up calls were made in the face of profound disagreements on social media platforms and online networks about the value and efficacy of the vaccines. Thus, this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…In total, 18% (8/45) of the studies showed a moderate risk of bias [ 43 - 46 , 53 - 56 ]. Finally, 27% (12/45) of the included studies showed a high risk of bias [ 57 - 68 ]. Of the 45 studies, in 1 (2%) study [ 69 ], none of the questions in the JBI tool were applicable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 18% (8/45) of the studies showed a moderate risk of bias [ 43 - 46 , 53 - 56 ]. Finally, 27% (12/45) of the included studies showed a high risk of bias [ 57 - 68 ]. Of the 45 studies, in 1 (2%) study [ 69 ], none of the questions in the JBI tool were applicable.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 45 included studies, 18 (40%) studies reported misinformation across all 3 categories [ 27 - 29 , 35 - 37 , 45 , 48 , 49 , 51 , 55 , 57 , 58 , 60 - 62 , 67 , 68 ], 9 (20%) studies reported only on conspiracies [ 26 , 30 , 33 , 42 , 44 , 46 , 53 , 54 , 56 ], 6 (13%) studies were concerned specifically with medical misinformation [ 25 , 34 , 38 , 43 , 63 , 64 ], and 12 (27%) studies reported on COVID-19 vaccine misinformation or antivaccine discourse without going into further detail [ 31 , 35 , 39 - 41 , 47 , 52 , 59 , 65 , 66 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…For the purposes of this study, VSC was conducted based on the lexical semantic properties of the linguistic content of the tweets. VSC is one of the most appropriate classification methods for opinion mining applications [48][49][50]. The steps are described in the following sub-sections.…”
Section: Methods Data and Proceduresmentioning
confidence: 99%
“…Governments must ensure that their citizens have access to reliable evidence-based information about the COVID-19 vaccine to make informed vaccination decisions (Alliheibi et al, 2021). An inclusive communication plan should be designed to address stakeholder questions through a process that the community and health care professionals must undertake and implement.…”
Section: Public Sentiment Around the Covid-19 Vaccine On Twittermentioning
confidence: 99%